Assessment Framework for Gamified Environments: A Gamification Assessment Model for Implementing the Framework (2018)
Gamification is a recent strategy used in several contexts like marketing, education and public health. We implement gamification as a strategy to promote a dynamic environment in Software Process Improvement initiatives. However, there are insufficient well-established theoretical guidelines for design and assess gamified experiences. Our research is oriented to the use of a framework for assessing gamified environments, which comprises the identification and adoption of gamification principles, as well as a design method for gamified activities. This framework is a proposal for the assessment of gamified environments looking for assure that gamified experiences meet the purposes, goals, principles and elements that are defined as gamification fundamental components. In this paper, we present a gamification assessment model for implement the framework that allows to calculate the level of gamification of a gamified environment. Such model is applied in an environment called Video Scrum and allows to verify gamification level from measurement rules. © 2018, Springer Nature Switzerland AG.